1997
DOI: 10.1074/jbc.272.1.69
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Mechanism for the Reductive Unfolding of Disulfide-containing Proteins

Abstract: Reductive unfolding of disulfide-containing proteins can be experimentally dissected into two distinct stages. In the presence of denaturant and thiol catalyst, native proteins unfold by reshuffling their native disulfides and convert to a mixture of scrambled structures. Subsequent reduction of the disulfide bonds of scrambled proteins requires only mild concentration of reductant (0.2-0.5 mM reduced dithiothreitol) and undergoes intermediates that consist of highly heterogeneous disulfide isomers. These prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 44 publications
1
60
0
Order By: Relevance
“…The mechanism of "all-or-none" disulfide reduction has been shown in numerous single domain proteins (11). The dramatic difference in stability between the native and non-native (scrambled) disulfide bonds has also been demonstrated in other proteins.…”
Section: Std X-pci)mentioning
confidence: 94%
See 2 more Smart Citations
“…The mechanism of "all-or-none" disulfide reduction has been shown in numerous single domain proteins (11). The dramatic difference in stability between the native and non-native (scrambled) disulfide bonds has also been demonstrated in other proteins.…”
Section: Std X-pci)mentioning
confidence: 94%
“…Unlike the native disulfide bonds that are stabilized by noncovalent interactions, non-native disulfide bonds of scrambled proteins are considerably more fragile and can be readily reduced by 0.5-1 mM dithiothreitol within 5-10 min of incubation at room temperature. This phenomenon has been shown with scrambled isomers of RNase A (26), hirudin, and tick anticoagulant peptide (11).…”
Section: Std X-pci)mentioning
confidence: 95%
See 1 more Smart Citation
“…[9][10][11][12] Reductive unfolding, the converse of oxidative folding, is the process by which a disulfidebond-containing protein loses its native structure (unfolds) through the (successive) reduction of its disulfide bonds. [13][14][15][16][17][18][19][20][21] In reductive unfolding, protein disulfide bonds scattered throughout the macromolecular architecture can serve as reporter groups for probing local fluctuations within the folded polypeptide; these fluctuations eventually lead to the unfolding of the whole molecule. 17 By assessing the relative susceptibilities of individual disulfide bonds to reduction by an extrinsic reducing agent such as dithiothreitol (DTT red ), it is possible to determine whether a particular disulfide bond is preferentially reduced; the region in which the easily reducible disulfide bond resides is the most flexible one and, therefore, prone to unfolding.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, isomerization of disulfides was shown to be an obligate step of the protein folding pathway (24), but recently it has been demonstrated that isomerization could also occur upon an unfolding triggered by disulfide reduction (25). Correct protein folding is considered to be catalyzed by protein-disulfide isomerase (26), which is a strong oxidant.…”
Section: Table III Kinetic Parameters Of Mutant Nadp-mdhsmentioning
confidence: 99%